Serum free carnitine levels in children with Kawasaki disease. Issue 1 (27th February 2022) - Muto, Taichiro; Nakamura, Nami; Masuda, Yu; Numoto, Shingo; Kodama, Shunsuke; Miyamoto, Ryosuke; Hayakawa, Tomohito; Mori, Hiromitsu; Iwayama, Hideyuki; Kurahashi, Hirokazu; Agata, Hiroatsu; Okumura, Akihisa
Abstract: Background: Carnitine plays an essential role in the transfer of long‐chain fatty acids to the mitochondria for β‐oxidation. No study has characterized carnitine in children with Kawasaki disease (KD). The objective of this study was to elucidate the characteristics of serum free carnitine (FC) in hospitalized pediatric patients with KD. Methods: We retrospectively analyzed 45 patients with KD in whom serum FC levels were measured. We investigated the clinical and laboratory parameters before intravenous immunoglobulin was administered, including serum FC levels, according to the response to intravenous immunoglobulin (IVIG). We also analyzed the relationship among serum FC, laboratory data, and clinical variables. Results: IVIG was effective in 33 children (responders) and was ineffective in 12 children (non‐responders). Serum FC levels were higher in non‐responders than in responders: 35.3 μmol/L (range, 26.8–118.4 μmol/L) vs 31.4 μmol/L (range, 20.9‐81.2 μmol/L), P <0.05. FC levels before IVIG in 80% of responders were below the normal range. The levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), total bilirubin, and FC were higher in non‐responders than in responders. FC levels were correlated with AST ( R 2 = 0.364, P = 0.0015) and ALT ( R 2 = 0.423, P < 0.001) levels. Conclusions: Free carnitine levels were elevated in some patients with KD, especially in those who were refractory to IVIG. Additionally, FC levels in children with KD correlated with ASL and ALT levels.